2023
DOI: 10.1101/2023.07.24.550434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gas vesicle-blood interactions enhance ultrasound imaging contrast

Bill Ling,
Jeong Hoon Ko,
Benjamin Stordy
et al.

Abstract: Gas vesicles (GVs) are genetically encoded, air-filled protein nanostructures of broad interest for biomedical research and clinical applications, acting as imaging and therapeutic agents for ultrasound, magnetic resonance, and optical techniques. However, the biomedical applications of GVs as a systemically injectable nanomaterial have been hindered by a lack of understanding of GVs’ interactions with blood components, which can significantly impactin vivoperformance. Here, we investigate the dynamics of GVs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…To this end, recent studies have shown that some immunogenicity exists for wild‐type GVs, as expected for bacteria‐derived protein sequences, and demonstrated that the biocompatibility of GVs can be substantially enhanced through surface coating, such as polyethylene glycol (PEG) modification. [ 66–69 ] Since 50 nm GVs use protein sequences originating from these wild‐type GVs, we anticipate a similar level of immunogenicity and opportunities for reducing immunogenicity through surface modification. Secondly, the ultrasound pressure and mechanical index needed to be determined for the efficient collapse of 50 nm GVs in in vivo applications.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, recent studies have shown that some immunogenicity exists for wild‐type GVs, as expected for bacteria‐derived protein sequences, and demonstrated that the biocompatibility of GVs can be substantially enhanced through surface coating, such as polyethylene glycol (PEG) modification. [ 66–69 ] Since 50 nm GVs use protein sequences originating from these wild‐type GVs, we anticipate a similar level of immunogenicity and opportunities for reducing immunogenicity through surface modification. Secondly, the ultrasound pressure and mechanical index needed to be determined for the efficient collapse of 50 nm GVs in in vivo applications.…”
Section: Discussionmentioning
confidence: 99%